2016
DOI: 10.1111/bjh.14399
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic intensity and survival differences in young patients with diffuse large B‐cell lymphoma: a Swedish Lymphoma Registry study

Abstract: Summary Young patients with diffuse large B‐cell lymphoma (DLBCL) are variably treated with rituximab combined with cyclophosphamide‐doxorubicin‐vincristine‐prednisone (R‐CHOP), CHOP‐etoposide (R‐CHOEP), and anthracycline‐based regimens with the addition of high‐dose cytarabine/methotrexate (R‐HDA/M). Using the nationwide, population‐based Swedish Lymphoma Registry, we evaluated outcome, by treatment and Healthcare Region, in all 751 DLBCL patients aged ≤60 years without central nervous involvement, diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A variety of studies have been undertaken to improve upon outcome achieved with R-CHOP. More intensive chemotherapy regimens have been comparatively studied in younger cohorts, with variable results [17][18][19][20]. Advances beyond R-CHOP, with the addition of agents as bortezomib [21][22][23], everolimus [24], ibrutinib [25][26][27], and lenalidomide [28][29][30], have been limited to-date.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have been undertaken to improve upon outcome achieved with R-CHOP. More intensive chemotherapy regimens have been comparatively studied in younger cohorts, with variable results [17][18][19][20]. Advances beyond R-CHOP, with the addition of agents as bortezomib [21][22][23], everolimus [24], ibrutinib [25][26][27], and lenalidomide [28][29][30], have been limited to-date.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, recent retrospective studies have shown that addition of HD-Mtx to a CHOP/R-CHOP regimen improves the prognosis of patients with high-risk DLBCL, irrespective of their risk for CNS relapse. [31][32][33] Whether or to what extent the low number of CNS relapses observed in our study is a consequence of a systemic efficacy of early administration of HD-Mtx needs to be confirmed in a randomized study.…”
Section: Discussionmentioning
confidence: 82%
“…Ah andfulo fc ombinations of chemotherapeutic treatments is routinely appliedt ot he patientss uffering from DLBCL. [45] Amongt hese chemotherapeutic drugs, we have chosen three most commond rugsd oxorubicin, etoposide and prednisolone for our current study. [37,[46][47][48] Prednisolone is the active form of pro-drugp rednisone, after metabolism in the liver.…”
Section: Resultsmentioning
confidence: 99%